PENERAPAN QUIZIZZ BERBASIS WEB PADA MATERI PENYAJIAN DATA KELAS VII MTs NEGERI 02 PONTIANAK - Fany Fajrianti; Dede Suratman; Dian Ahmad B (Universitas Tanjungpura, 2022)
The purpose of this study was to obtain information and an overview of the steps in using Quizizz, student activities, and student responses regarding the use of Quizizz. The research method used is qualitative with a qualitative descriptive approach. subjects in this study were 35 students. data collection was done using observation, interviews, and questionnaires. The data analysis technique used is according to (Miles & Huberman) namely data reduction, data presentation, and conclusions. The results indicated that the steps of using Quizizz went smoothly and got the students' enthusiasm for learning increased. By utilizing quizizz students are only required to log in to the quiz link, and write the join code, and the students' name. Students' activities related to the usage of Quizizz were obtained from observations using 3 indicators, namely listening activities, visual activities, and oral activities. The results of this activity are included in the